2019
DOI: 10.1027/2151-2604/a000387
|View full text |Cite
|
Sign up to set email alerts
|

Seven Easy Steps to Open Science

Abstract: Abstract. The open science movement is rapidly changing the scientific landscape. Because exact definitions are often lacking and reforms are constantly evolving, accessible guides to open science are needed. This paper provides an introduction to open science and related reforms in the form of an annotated reading list of seven peer-reviewed articles, following the format of Etz, Gronau, Dablander, Edelsbrunner, and Baribault (2018) . Written for researchers and students – particularly in psychological scienc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 56 publications
0
77
0
1
Order By: Relevance
“…Crucially, it could also accelerate the production of much-needed evidence, especially if paired with open scientific principles such as open data, shared code, and preregistration ( Munafò et al, 2017 ; Vazire, 2018 ). By sharing data and materials, progress could be accelerated because researchers can easily build on (and check) others’ work ( Crüwell et al, 2019 ). Furthermore, by implementing preregistration and Registered Reports, false-positive rates and publication biases can be better controlled ( Chambers, 2013 ; Wagenmakers, Wetzels, Borsboom, van der Maas & Kievit, 2012 ).…”
Section: Looking Aheadmentioning
confidence: 99%
“…Crucially, it could also accelerate the production of much-needed evidence, especially if paired with open scientific principles such as open data, shared code, and preregistration ( Munafò et al, 2017 ; Vazire, 2018 ). By sharing data and materials, progress could be accelerated because researchers can easily build on (and check) others’ work ( Crüwell et al, 2019 ). Furthermore, by implementing preregistration and Registered Reports, false-positive rates and publication biases can be better controlled ( Chambers, 2013 ; Wagenmakers, Wetzels, Borsboom, van der Maas & Kievit, 2012 ).…”
Section: Looking Aheadmentioning
confidence: 99%
“…This approach is meant to eschew a "one size fits all" mentality. The four principles are broadly applicable to any area of study, but the specific behavioral manifestations will always be contextualized by the research question and methodology (Crüwell et al, 2019).…”
Section: The Open Science Movementmentioning
confidence: 99%
“…Similarly, Camerer et al (2018) reported attempts to replicate 21 experiments originally published in Nature and Science, with less than two thirds succeeding. Replication attempts can fail for any of several reasons (e.g., maybe the replication did not properly recreate the essential conditions under which the original effect was obtained, or maybe the failure was just a Type II error), but most attention has focused on the role of faulty research practices in the original research, leading to calls for methodological reform to correct those practices and make psychological science more cumulative and useful (Bishop, 2019;Chambers, 2017;Crüwell et al, 2019;Frith, 2019;Munafo, 2017;Nelson, Simmons, & Simonsohn, 2018;Spellman, 2015).…”
Section: Seven Steps Toward Transparency and Replicability In Psycholmentioning
confidence: 99%